Aplikasi Manajemen Produksi Dalam Usaha Produksi Produk Kosmetik Tradisional: Desa Sukoanyar, Kecamatan Wajak, Kabupaten Malang - Dita Rachmawati; Ferra Eka Ramadhani; Mudji; Nigi Prawitasari; Nanda Sisdianto; Diana Alfiyanti (JOURNAL INNOVATION AND COMMUNITY SERVICE, 2023)
Production management is a business activity carried out within a firm, and its processing operations include planning, organizing, directing, and managing activities in order to achieve a certain company objective in an effective and efficient manner. Production management exists in a firm to guarantee that the actions scheduled are in agreement with the company’s targets and can meet the company’s goals. This production management may also increase the company’s performance, making it more effective and efficient. Many parties within the company, both departments and divisions within the company, must support company managers in analyzing, conducting work assessments, and providing important information related to production activities in order for the company to grow and create good performance. Of course, effective collaboration between bosses and employees is required. Production management within the company is very important because it can increase the company’s competitiveness and allow it to carry out its operational activities more efficiently and effectively, allowing the company to avoid waste—a waste of resources that can harm the company.